Lipofectin increases the specific activity of cypovirus particles for cultured insect cells. - Hill, C; Booth, T; Stuart, D; Mertens, P (1999)
Cytoplasmic polyhedrosis viruses (CPV) are classified as 14 distinct species (electropherotypes) within the genus Cypovirus, family Reoviridae. Cypovirus research has been limited by a lack of appropriate cell culture systems (for each of these virus species) in which the majority of cells can become productively infected. Lipofection increased the infection rate of Lymantria dispar 652 cells, by virus particles (derived from polyhedra) of Orgyia pseudosugata type 5 cypovirus (Op-5 CPV), from 3 to 44%. Lipofection also significantly increased the percentage of Trichoplusia ni 368 cells infected with the same virus (from < 1 to approximately 7%). The spread of cypovirus infection between cells was either very slow or insignificant, and infected cells appeared to remain viable for long periods. Virus infection was detected by the observation of polyhedra formation in individual cells and it was therefore possible to develop a simple quantitative assay system to measure virus titre (TCID50). Cryo-electron microscopy showed that cypovirus particles formed a complex with the lipid, involving their envelopment within the liposome membrane. It was concluded that the increased infectivity of the virus by lipofection was due to a more efficient cell entry mechanism, probably involving fusion between liposome and cell membranes.